Investigation of airborne trace element pollution in Hai Phong city (Vietnam) using Barbula Indica moss and neutron activation analysis - Le Hong Khiem, Inga Zinicovscaia, Trinh Thi Thu My, Marina Frontasyeva, Nguyen Thi Bao My, Nguyen An Son, Dinh Van Trung, Le Dai Nam, Nguyen Thi Minh Sang, Nguyen Ngoc Duy, Nguyen Quang Hung, Bui Van Hai, Nguyen Ngoc Mai, Duong Duc Thang, Nguyen Thi Dinh (2023)
This paper presents the results of the frst observation of airborne trace elements using Barbula Indica moss in Hai Phong city, one of the two largest seaport cities in Vietnam. A total of 39 moss samples were collected at 39 diferent locations in January 2020 in Hai Phong. Neutron activation analysis method was used to analyze the concentration of 36 chemical elements in the collected moss samples and the obtained data were compared with the data obtained in other regions of Vietnam, China and Europe. The level of chemical elemental contamination in the air of Hai Phong was categorized and the possible sources of pollutant emissions were identifed by applying principal component analysis.